THE EFFECT OF FINANCIAL LITERACY AND POCKET MONEY ON STUDENTS' FINANCIAL MANAGEMENT BEHAVIOR THROUGH FINANCIAL SELF-EFFICACY (A STUDY OF ACTIVE FEB STUDENTS AT STATE UNIVERSITY OF MAKASSAR) - Fakhirah Husain; Adhiba Nur Fayyad; Imelda; Icha Patadungan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the role of financial literacy and pocket money on students' financial management behavior, with financial self-efficacy as an intervening variable. The phenomenon of increasing student consumer behavior is the main background of this study. Using a quantitative explanatory approach with SEM-PLS analysis on 130 active students of the Faculty of Economics and Business, Makassar State University, the results show that financial literacy and pocket money have a positive effect on financial self-efficacy, and financial self-efficacy has a significant effect on financial management behavior. However, financial literacy does not have a direct effect without the mediation of financial self-efficacy. This means that the higher the financial literacy and pocket money accompanied by self-confidence in managing finances, the better the students' financial behavior in planning and controlling expenses wisely.